Impact of Holding a Badminton Racket on Spatio-Temporal and Kinetic Parameters During Manual Wheelchair Propulsion - Alberca, Ilona; Chénier, Félix; Astier, Marjolaine; Combet, Marion; Bakatchina, Sadate; Brassart, Florian; Vallier, Jean-Marc; Pradon, Didier; Watier, Bruno; Faupin, Arnaud (Frontiers in Sports and Active Living, 2022)
Introduction: Para badminton entered the Paralympic world for the first time with the 2021 Paralympic Games in Tokyo. The particularity of this sport lies in the handling of the wheelchair and the racket simultaneously. To our knowledge, and considering the youthfulness of this sport, it appears no study has looked at the impact of the badminton racket on kinetic and spatiotemporal parameters. Therefore, the aim of our study was to investigate the impact of the badminton racket on the amplitude of kinetic and spatiotemporal parameters of wheelchair propulsion, considered as propulsion effectiveness and risk of injury criteria. We hypothesized that holding a badminton racket while propelling the wheelchair modifies the kinetics and temporal parameters of the athlete's propulsion due to the difficulty to hold the handrim, therefore decreasing propulsion effectiveness and increasing risk of injury. Materials and methods: 16 able-bodied were introduced to para badminton for 6 sessions of 90min. No injuries hindered their propulsion. They had to propel with and without a racket held on the dominant side along a 20m straight line at a constant velocity of 5 km/h. They all used the same sports wheelchair equipped with two instrumented wheels (SmartWheel). Results: Participants increased their maximal total force and force rate of rise but decreased their fraction of effective force with their dominant hand compared to the non-dominant hand when using a racket. In addition, they decreased their fraction of effective force, push time, cycle time and push angle, and increased their maximal propulsive moment, maximal total force, and force rate of rise when comparing the same dominant hand with and without the racket. Discussion: Using a badminton racket modifies the athlete's force application in a way that is generally related to a lower propulsion effectiveness and a higher risk for injury. Indeed, it seems that propulsion with a racket prevents from correctly grabbing the handrim.